CdS (at) MoS2 photocatalyst, preparation method thereof and application of CdS (at) MoS2 photocatalyst in biomass reforming hydrogen production
By adopting CdS@MoS2 photocatalyst and using thiourea as the sulfur source, the synthesis process is simplified and the purity of the product is improved. The problems of photocorrosion and low quantum efficiency of CdS photocatalyst in biomass reforming are solved, and a more efficient photocatalyst is achieved. Catalytic hydrogen production effect and stability.
Patent Information
- Application Number
- CN202411380140.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-21
AI Technical Summary
The existing CdS photocatalysts have photocorrosion problems and low quantum efficiency during their application, which limits their long-term application in biomass reforming.
Using CdS@MoS2 photocatalyst, CdS and MoS2 were synthesized separately by uniformly using thiourea as the sulfur source, and using the stirring method to obtain CdS@MoS2, which simplified the synthesis process and improved the purity of the product.
It reduces the recombination rate of electron-hole pairs, accelerates the space charge transfer between interfaces, extends the lifetime of photogenerated carriers, improves the efficiency of photocatalytic hydrogen production, and shows good stability.
Smart Images

Figure CN119327487A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysis, and in particular relates to a CdS@MoS2 photocatalyst and a preparation method thereof, and an application of biomass reforming to produce hydrogen. Background Art
[0002] In view of the continued aggravation of the energy crisis and environmental pollution problems, the development of renewable energy and clean fuel technology is particularly urgent and important. As a renewable organic matter, biomass has received increasing attention in energy conversion and environmental improvement, especially in the process of exploring sustainable carbon cycle solutions. Since Honda and Fujishima discovered in 1972 that TiO2 can decompose water into hydrogen and oxygen under ultraviolet light, the research on photocatalysts has made rapid progress. Among them, metal sulfides, especially cadmium sulfide (CdS) with excellent light absorption performance and high photocatalytic activity and molybdenum disulfide (MoS2) with unique layered structure and electronic properties, have shown important application value in the field of photocatalytic biomass reforming.
[0003] Although CdS, as an efficient photocatalyst, can effectively convert solar energy into chemical energy, thereby promoting the photocatalytic reforming of biomass molecules, there are still many problems in its application process. Specifically, the electrons and holes generated by CdS in the photocatalytic process can participate in the redox reaction of biomass molecules to generate valuable chemical products. However, the photocorrosion problem of CdS and the low quantum efficiency seriously restrict its long-term application in biomass reforming. Patent CN105688945A discloses a molybdenum disulfide (MoS2) nanosheet / cadmium sulfide (CdS) nanowire core-shell structure composite photocatalyst and its preparation method, which is a one-dimensional CdS nanowire as a core and a two-dimensional MoS2 nanosheet as a shell, and is composited by a hydrothermal method through an electrostatic self-assembly method. However, the synthesis method of the composite material proposed in the patent is complicated, and copper reagents need to be used when synthesizing CdS, which will cause copper reagents to remain, and acid needs to be used for purification treatment later; secondly, in terms of photocatalytic hydrogen production, biomass reforming hydrogen production technology is not involved. Summary of the invention
[0004] The purpose of the present invention is to provide a CdS@MoS2 photocatalyst and its preparation method and application in order to overcome the defects of the above-mentioned prior art. This patent uses thiourea as a sulfur source when synthesizing the catalyst, avoids the use of excessive reagents, and reduces costs; and synthesizes CdS and MoS2 separately, thereby improving the purity of the product; finally, CdS@MoS2 is obtained by stirring, and the synthesis method is easy to operate; and sucrose is used as a hydrogen production substrate, which provides a new direction for biomass reforming hydrogen production. This catalyst is prepared by the following method: the prefabricated CdS powder is dispersed in deionized water and stirred with a magnetic stirrer for 1 to 2 hours, and then MoS2 dispersed in deionized water and ultrasonically treated for 1 to 2 hours is added, wherein the mass ratio of MoS2 to CdS is 0.02:1 to 0.1:1, and the mixture is stirred at room temperature for 24 hours by a magnetic stirrer, and finally the mixed solution is centrifuged and dried to obtain a CdS@MoS2 photocatalyst. The photocatalyst of the present invention reduces the recombination rate of electron-hole pairs, accelerates spatial charge transfer between interfaces, and prolongs the life of photogenerated carriers. The experiment is easy to operate, low in cost, and has good stability. It exhibits good photocatalytic hydrogen production efficiency and has great development potential in photocatalytic biomass conversion.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] In one aspect, the present invention provides a method for preparing a CdS@MoS2 photocatalyst, comprising the following steps: firstly, prefabricated CdS powder is dispersed in deionized water and stirred by a magnetic stirrer for 1 to 2 hours, then MoS2 dispersed in deionized water and ultrasonically treated for 1 to 2 hours is added, wherein the mass ratio of MoS2 to CdS is 0.02:1 to 0.1:1, and the mixture is stirred at room temperature for 24 hours by a magnetic stirrer, and finally the mixed solution is centrifuged and dried to obtain a CdS@MoS2 photocatalyst. According to the method for preparing a photocatalyst according to claim 1, the mass ratio of MoS2 to CdS is preferably 0.04:1.
[0007] Furthermore, the preparation method includes the following steps: dispersing CdS material in deionized water and stirring to obtain a CdS dispersion; dispersing MoS2 material in deionized water for ultrasonic treatment, adding it to the CdS dispersion, and centrifugally drying to obtain the CdS@MoS2 photocatalyst; the mass ratio of the CdS material to the MoS2 material is (0.02-0.1):1.
[0008] Furthermore, the preparation of CdS material includes the following process:
[0009] Cadmium acetate dihydrate and thiourea are dissolved in ethylenediamine solvent, stirred, heated to 180° C. and maintained for 24 hours, and washed and dried to obtain CdS material.
[0010] Furthermore, the molar ratio of cadmium acetate dihydrate to thiourea is 1:3; the stirring is magnetic stirring, and the stirring time is 2 to 3 hours; the washing is washing three times in sequence with distilled water and ethanol; and the drying is drying in a vacuum oven at 60° C. for 8 to 10 hours.
[0011] Furthermore, the preparation of MoS2 material includes the following process:
[0012] Sodium molybdate was dissolved in deionized water, thiourea was added, and the mixture was sealed and heated to 200°C and maintained for 24 hours. After cooling, the MoS2 material was obtained by centrifugal drying.
[0013] Furthermore, the molar ratio of sodium molybdate to thiourea is 1:7.5; the stirring is magnetic stirring, and the stirring time is 1 to 2 hours; the washing is sequentially washed with distilled water and ethanol; and the drying is dried in a vacuum oven at 60°C for 8 to 10 hours.
[0014] Furthermore, the preparation method comprises the following steps:
[0015] (1) Preparation of CdS material. As a specific embodiment of the present invention, the CdS material is prepared by the following steps:
[0016] Cadmium acetate dihydrate and thiourea are dissolved in ethylenediamine solvent, and magnetic stirring is used to ensure uniform mixing of the precursors and complete dissolution of the reactants; the solution is then transferred to a 100 mL reactor, heated to 180° C. and maintained for 24 hours; finally, the product is cooled, centrifuged, washed and dried to obtain CdS material.
[0017] (2) Preparation of MoS2 material. As a specific embodiment of the present invention, the MoS2 material is prepared by the following steps:
[0018] Sodium molybdate was dissolved in deionized water, and then thiourea was added to the solution. Magnetic stirring was used to ensure uniform mixing of the precursors and complete dissolution of the reactants. The solution was then transferred to a 100 mL reactor, heated to 200 ° C and maintained for 24 hours. Finally, the product was cooled, centrifuged, washed and dried to obtain MoS2 material.
[0019] (3) Preparation of CdS@MoS2 material. As a specific embodiment of the present invention, the composite material is prepared by the following steps:
[0020] The CdS powder in step (1) is dispersed in deionized water and stirred with a magnetic stirrer for 1 to 2 hours (preferably 2 hours), and then the MoS2 dispersion obtained in method (2) after ultrasonic treatment for 1 to 2 hours (preferably 1 hour) is added, wherein the mass ratio of MoS2 to CdS is 0.02:1 to 0.1:1, preferably 0.04:1. The mixture is stirred for 24 hours at room temperature with a magnetic stirrer, and finally the mixed solution is centrifuged and dried to obtain a CdS@MoS2 photocatalyst.
[0021] In a second aspect, the present invention provides a CdS@MoS2 photocatalyst, which is prepared by any of the preparation methods described above.
[0022] Further, the MoS2 layer is deposited on the CdS crystal in an amorphous form.
[0023] In a third aspect, the present invention provides an application of a CdS@MoS2 photocatalyst in photocatalytic sucrose hydrogen production.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] (1) The photocatalyst of the present invention reduces the recombination rate of electron-hole pairs, accelerates the spatial charge transfer between interfaces, and prolongs the life of photogenerated carriers. The experiment is easy to operate, low in cost, and has good stability. It shows good photocatalytic hydrogen production efficiency and has great development potential in photocatalytic biomass conversion. The photocatalyst of the present invention has a built-in electric field, which is conducive to improving the charge separation efficiency and has a good effect on photocatalytic biomass reforming hydrogen production, especially sucrose hydrogen production.
[0026] (2) The photocatalyst of the present invention has the best dispersibility and no obvious agglomeration phenomenon, which provides a more heterogeneous catalytic environment for the photocatalyst.
[0027] (3) The photocatalyst of the present invention enhances the separation efficiency of photogenerated charge carriers, thereby improving the photocatalytic activity.
[0028] (4) The photocatalyst of the present invention can photocatalytically reform sucrose to produce hydrogen and has a high hydrogen production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Performance test diagrams of CdS and composite materials (CdS@MoS2) with different proportions, where (a) is the photocatalytic hydrogen production curve and (b) is the hydrogen production rate.
[0030] Figure 2These are the performance test diagrams of CdS, MoS2 and composite material MC-x (x=2, 4, 6, 10), where (a) is the XRD spectrum of CdS, MoS2 and composite material MC-x (x=2, 4, 6, 10), and (b) is the Raman spectrum of CdS, MoS2 and composite material MC-x (x=2, 4, 6, 10).
[0031] Figure 3 The X-ray photoelectron spectrum of the MC-4 composite material, where (a) is S2p, (b) is Mo 3d, and (c) is Cd3d. The black line represents the change peak of the element orbital, and the blue and red lines represent the standard peaks of the elements in the sample.
[0032] Figure 4 Performance test diagrams of CdS, MoS2 and composite materials, where (a) is the UV-vis DRS spectra of CdS, MoS2 and composite materials, and (b) is the energy band spectrum of CdS and MC-4.
[0033] Figure 5 Performance test diagrams of CdS, MoS2 and MC-4, where (a) is the Nyquist impedance spectrum and (b) is the transient photocurrent response spectrum.
[0034] Figure 6 The performance test diagrams of CdS and MC-4, where (a) is the transient OCVD measurement diagram under visible light irradiation, and (b) is the average lifetime diagram of photogenerated carriers in OCVD measurement.
[0035] Figure 7 NMR product analysis chart.
[0036] Figure 8 The reaction mechanism diagram. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0038] Features such as component models, material names, connection structures, control methods, algorithms, etc. that are not clearly stated in this technical solution shall be deemed as common technical features disclosed in the prior art.
[0039] It should be noted that, in the present invention, relational terms such as first and second, etc. are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations.
[0040] In the following examples, raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.
[0041] Example 1
[0042] Preparation of CdS and MoS2 photocatalysts
[0043] The present embodiment provides a method for preparing CdS, comprising the following steps: dissolving 15 mmol of cadmium acetate dihydrate and 45 mmol of thiourea in 60 mL of ethylenediamine solvent, and stirring at room temperature for 3 h using a magnetic stirrer. After stirring, the resulting solution is transferred to a reactor with a capacity of 100 mL, and the reaction time is maintained at a temperature of 180 ° C for 24 h. After the reaction is completed, the reactor is naturally cooled to room temperature, and then the product is separated into solid and liquid by centrifugation, and the separated precipitate is washed three times in sequence with distilled water and ethanol. Finally, CdS is obtained by drying in a vacuum oven at 60 ° C for 8 h.
[0044] The present embodiment provides a method for preparing MoS2, comprising the following steps: dissolving 2 mmol of sodium molybdate in 60 mL of deionized water. Subsequently, 15 mmol of thiourea is added to the solution and stirred at room temperature for 1 hour using a magnetic stirrer. After stirring, the mixed solution is transferred to a 100 mL high pressure reactor. The reactor is sealed and heated at a high temperature of 200 ° C for 24 hours. After the reaction is completed, it is slowly cooled to room temperature, and then the reaction product is separated from the solvent by centrifugation. The separated precipitate is washed with distilled water and ethanol several times. Finally, the washed sample is placed in a 60 ° C oven and dried for 8 hours to obtain pure MoS2.
[0045] Example 2
[0046] Preparation of CdS@MoS2 photocatalyst
[0047] The present embodiment provides a method for preparing CdS@MoS2, comprising the following steps: using CdS and MoS2 obtained in Example 1, 250 mg of CdS powder is uniformly dispersed in 50 mL of deionized water, and fully stirred for 2 hours by a magnetic stirrer to obtain a CdS solution. At the same time, according to the mass ratio of 2% MoS2 / CdS, MoS2 powder is dispersed in another 50 mL of deionized water to obtain a MoS2 solution. Subsequently, the MoS2 solution is placed in an ultrasonic bath for ultrasonic treatment for 1 hour, and then continued to be stirred for 1 hour by a magnetic stirrer. After stirring, the MoS2 solution is slowly poured into the CdS solution and continued to stir at room temperature for 24 hours. After mixing, CdS@MoS2 is obtained by centrifugation and drying (the centrifugal speed is 7930 rpm, the centrifugal time is 10 minutes, and the drying is placed in a 60°C oven for drying for 8 hours), and is named MC-2.
[0048] Example 3
[0049] Preparation of CdS@MoS2 photocatalyst
[0050] The present embodiment provides a method for preparing CdS@MoS2, comprising the following steps: using CdS and MoS2 obtained in Example 1, 250 mg of CdS powder is uniformly dispersed in 50 mL of deionized water, and fully stirred for 2 hours by a magnetic stirrer to obtain a CdS solution. At the same time, according to the mass ratio of 4% MoS2 / CdS, MoS2 powder is dispersed in another 50 mL of deionized water to obtain a MoS2 solution. Subsequently, the MoS2 solution is placed in an ultrasonic bath for ultrasonic treatment for 1 hour, and then continued to be stirred for 1 hour by a magnetic stirrer. After stirring, the MoS2 solution is slowly poured into the CdS solution and continued to stir at room temperature for 24 hours. After mixing, CdS@MoS2 is obtained by centrifugation and drying (the centrifugal speed is 7830 rpm, the centrifugal time is 10 min, and the drying is placed in a 60 ° C oven for 8 hours) and named MC-4.
[0051] Example 4
[0052] Preparation of CdS@MoS2 photocatalyst
[0053] Preparation of CdS@MoS2: 250 mg of CdS powder was evenly dispersed in 50 mL of deionized water and stirred for 2 h by a magnetic stirrer. At the same time, MoS2 powder was dispersed in another 50 mL of deionized water according to a mass ratio of 6% MoS2 / CdS. Subsequently, the MoS2 solution was ultrasonically treated in an ultrasonic bath for 1 h, and then continued to be stirred for 1 h by a magnetic stirrer. After stirring, the MoS2 solution was slowly poured into the CdS solution and continued to stir at room temperature for 24 h. After mixing, CdS@MoS2 was obtained by centrifugation and drying at 7830 rpm for 10 min, named MC-6.
[0054] Example 5
[0055] Preparation of CdS@MoS2 photocatalyst
[0056] The present embodiment provides a method for preparing CdS@MoS2, comprising the following steps: using CdS and MoS2 obtained in Example 1, 250 mg of CdS powder is uniformly dispersed in 50 mL of deionized water, and fully stirred for 2 hours by a magnetic stirrer to obtain a CdS solution. At the same time, according to the mass ratio of 10% MoS2 / CdS, MoS2 powder is dispersed in another 50 mL of deionized water to obtain a MoS2 solution. Subsequently, the MoS2 solution is placed in an ultrasonic bath for ultrasonic treatment for 1 hour, and then continued to be stirred for 1 hour by a magnetic stirrer. After stirring, the MoS2 solution is slowly poured into the CdS solution and continued to stir at room temperature for 24 hours. After mixing, CdS@MoS2 is obtained by centrifugation and drying (the centrifugal speed is 7830 rpm, the centrifugal time is 10 minutes, and the drying is placed in a 60°C oven for drying for 8 hours), and is named MC-10.
[0057] The nanorod-like materials prepared by the above method are named MC-x, where 'x' represents the mass ratio of MoS2 to CdS.
[0058] As shown in Table 1, the specific surface areas (S BET ), pore volume and pore size. The composite materials synthesized at different ratios showed small differences in specific surface area and pore size, which indicates that the synthesis process can maintain the consistency of the pore properties of the materials at different ratios. Specifically, the data of specific surface area and pore volume, such as the specific surface area of MC-4 sample is 29.404m 2 ·g -1 , the pore volume is 0.249 cm 3 ·g -1The introduction of MoS2 did not significantly change the pore structure of the CdS substrate, and its effect on the overall performance of the composite material was negligible.
[0059] Table 1 Specific surface area, pore volume and pore size of composite materials with different ratios
[0060]
[0061] ①Investigate the hydrogen production efficiency of sucrose catalyzed by different catalysts
[0062] The specific experimental process is as follows: 2 g sucrose and 50 mg catalyst were added to 100 mL NaOH aqueous solution (1 mol·L -1 ). During the life test of the photocatalyst, 6 hours was set as a photocatalytic performance test cycle. After each cycle, the reacted catalyst was separated by centrifugation, then washed with water and ethanol and dried for the next cycle of testing.
[0063] Depend on Figure 1 It can be seen that by measuring the hydrogen production under continuous illumination conditions, as the MoS2 loading ratio increases, it is revealed that when the MoS2 content increases to 4% (MC-4), the photocatalytic hydrogen production activity reaches a peak, and then decreases as the MoS2 content further increases. The results show that the photocatalytic hydrogen production activity first increases and then decreases. There is an optimal value for the mass ratio of MoS2 to CdS, and its hydrogen production rate reaches 388.39μmol·g -1 ·h -1 , indicating that 4% MoS2 loading ratio is the optimal condition.
[0064] ②Catalyst characterization
[0065] For CdS@MoS2 and CdS and MoS2 prepared in Example 1, the catalyst composite condition was analyzed by XRD, the chemical structure of the catalyst was analyzed by Raman, the electronic structure of the catalyst was analyzed by XPS, the light absorption capacity of the catalyst was analyzed by UV-DRS, and the photoelectrochemical properties of the catalyst were analyzed (EIS, it, OCVD).
[0066] Depend on Figure 2 (a) It can be seen that when the loading amount of MoS2 increases from 2wt% to 10wt%, the diffraction peak of the CdS@MoS2 composite catalyst does not change significantly, indicating that the loading process of MoS2 does not change the crystal phase of the CdS catalyst, and the CdS in the composite catalyst maintains the same crystal structure, while the loading of MoS2 helps to separate charges and improve the photocatalytic activity. However, no obvious MoS2 signal is found in the spectrum of the MoS2@CdS sample, indicating that the MoS2 layer deposited on the CdS is amorphous. In addition, Figure 2 (b) It can be seen that for the CdS@MoS2 composite material, the Raman peaks of CdS still exist, but when the content of MoS2 gradually increases, the Raman peaks at 385 and 410 cm -1 The Raman characteristics of MoS2 were also detected, confirming the coexistence of CdS and MoS2 in the composite material.
[0067] Depend on Figure 3 It can be seen that S exists in the -2 valence state in CdS, but due to the surface effect of CdS nanorods and the possible interaction between sulfur atoms and Mo atoms at the interface with MoS2, the electronic structure of S is affected, resulting in changes in the XPS peak shape of S. In addition, the data show that Mo has only one peak, and it may exhibit different electronic structures in the composite material due to the interface with CdS. Charge transfer, changes in chemical bonding, or lattice distortion at these interfaces may cause changes in the XPS peak shape of Mo. In addition, the size effect and surface effect of the nanorod-like structure may also affect the XPS peak shapes of Cd, S, and Mo.
[0068] Depend on Figure 4 It can be seen that the band gap energy (Eg) of the pure CdS sample is 2.34eV, while the band gap energy of the MC-4 sample is reduced to 2.31eV. This reduced band gap energy indicates that by introducing MoS2, the MC-4 sample is able to expand its light absorption range in the visible light region, especially to the near-infrared region, which is crucial for improving the solar energy utilization efficiency of photocatalysts. Specifically, in samples MC-2 to MC-10, it can be observed that with the increase of MoS2 content, the absorption curve gradually enhances in the visible light region, indicating an increase in light absorption intensity. In particular, the MC-4 sample has a significantly higher absorption intensity than the pure CdS sample in the wavelength range of 400 to 600nm. This phenomenon may be related to the heterostructure formed between MoS2 and CdS, which may enhance light absorption and also promote the effective separation of photogenerated electrons and holes, thereby enhancing photocatalytic activity. However, when the MoS2 content is further increased, the enhancement trend of the light absorption performance slows down, which may indicate that there is an optimal MoS2 loading ratio. Beyond this ratio, excessive MoS2 may lead to saturation or even decrease of the light absorption performance.
[0069] Depend on Figure 5(a) It can be seen that the pure CdS sample exhibits a higher charge transfer impedance, which is reflected in the larger semicircle radius in its Nyquist plot. In contrast, the MoS2-loaded MC-x samples show a gradually decreasing semicircle radius, indicating a decrease in charge transfer impedance, which may be due to the fact that the introduction of MoS2 promotes charge separation and transport. In particular, the MC-4 sample shows the smallest semicircle radius among all composites, indicating that it has the lowest charge transfer impedance and the best electron transport performance. These results indicate that the electron transport efficiency of the photocatalyst can be significantly improved by optimizing the mass ratio of MoS2 to CdS, which is crucial for improving the photocatalytic performance. The excellent electron transport properties of the MC-4 sample may originate from the good interfacial contact and effective electron coupling between MoS2 and CdS, which provides an effective way for the rapid separation of photogenerated electrons and holes.
[0070] Depend on Figure 5 (b) It can be seen that at the beginning of illumination, the MC-4 sample rapidly generates photocurrent, and its photocurrent intensity is higher than that of the pure CdS sample, which indicates that the MC-4 sample has a more effective separation efficiency of photogenerated charge carriers. As the illumination stops, the photocurrent of the MC-4 sample decays slowly, suggesting a longer charge carrier lifetime, which is crucial for improving the charge utilization efficiency in the photocatalytic process. In addition, the MC-4 sample shows excellent cyclic stability over multiple light-dark cycles, confirming its potential long-term operational stability in practical photocatalytic applications. The transient photocurrent test results further confirm that the photoelectrochemical performance of CdS-based photocatalysts can be effectively improved by MoS2 loading.
[0071] Depend on Figure 6 It can be seen that the MC-4 sample exhibits a higher open circuit voltage (V oc ), which indicates its better separation efficiency of photogenerated electron-hole pairs. In addition, the V oc The slower decay rate indicates that its charge carriers have a longer lifetime, which helps to improve the charge utilization efficiency in the photocatalytic process. These results further confirm that by optimizing the loading amount of MoS2, not only the light absorption capacity is enhanced, but also the separation and transport characteristics of charge carriers are improved, which fully demonstrates the importance of MoS2 loading for improving the performance of CdS-based photocatalysts.
[0072] ③Photocatalytic reforming process and catalytic principle
[0073] By analyzing the 1H nuclear magnetic resonance (NMR) spectrum with heavy water (D2O) as solvent ( Figure 7), we found that under photocatalysis, sucrose was mainly converted into glucose and fructose, and the intermediate product was organic acid, which was consistent with the expected biomass depolymerization reaction. In addition, oxidation products such as gluconic acid and sorbitol were identified through the observed NMR signal changes, which indicated that during the photocatalytic process, some sucrose molecules underwent oxidation reactions to produce chemicals with added value. Based on these findings, a possible reaction pathway for photocatalytic reforming of sucrose to produce hydrogen was proposed. In this pathway, the photocatalyst generates electron-hole pairs under light excitation. The electrons participate in the reduction reaction of sucrose to produce hydrogen, while the holes react with water or oxygen to produce oxidants, thereby promoting the oxidation of sucrose ( Figure 8 ).
[0074] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a CdS@MoS2 photocatalyst, characterized in that: The following steps are involved: Dispersing CdS material in deionized water, and stirring to obtain a CdS dispersion; The MoS2 material is dispersed in deionized water and subjected to ultrasonic treatment, and then added into the CdS dispersion during stirring, and the CdS@MoS2 photocatalyst is obtained after centrifugal drying.
2. The method for preparing a CdS@MoS2 photocatalyst according to claim 1, characterized in that: The preparation of CdS materials includes the following processes: Cadmium acetate dihydrate and thiourea are dissolved in ethylenediamine solvent, heated to 180° C. and maintained for 24 hours, cooled, washed and dried to obtain CdS material.
3. The method for preparing a CdS@MoS2 photocatalyst according to claim 2, characterized in that: The molar ratio of the cadmium acetate dihydrate to thiourea is 1:
3.
4. The method for preparing a CdS@MoS2 photocatalyst according to claim 1, characterized in that: The preparation of MoS2 material includes the following processes: Sodium molybdate was dissolved in deionized water, thiourea was added, stirred for the fourth time, sealed and heated to 200°C and maintained for 24 hours, and MoS2 material was obtained after cooling and drying.
5. The method for preparing a CdS@MoS2 photocatalyst according to claim 4, characterized in that: The molar ratio of sodium molybdate to thiourea is 1:7.
5.
6. The method for preparing a CdS@MoS2 photocatalyst according to claim 1, characterized in that: The mass ratio of the CdS material to the MoS2 material is (0.02-0.1):
1.
7. The method for preparing a CdS@MoS2 photocatalyst according to claim 6, characterized in that: The mass ratio of the CdS material to the MoS2 material is 0.04:
1.
8. A CdS@MoS2 photocatalyst, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 7.
9. A CdS@MoS2 photocatalyst according to claim 8, characterized in that: The MoS2 layer is deposited in an amorphous state on the CdS.
10. A use of a CdS@MoS2 photocatalyst prepared by the preparation method according to any one of claims 1 to 8 or a CdS@MoS2 photocatalyst according to claim 7, characterized in that: The CdS@MoS2 photocatalyst is used to photocatalytically produce hydrogen from sucrose.
Citation Information
Patent Citations
Composite photo-catalyst with molybdenum disulfide (MoS2) nanosheet / cadmium sulfide (CdS) nanowire core-shell structure
CN105688945A